PENGARUH ESKTRAKULIKULER PRAMUKA TERHADAP KARAKTER SEMANGAT KEBANGSAAN PESERTA DIDIK DI SMA NEGERI 12 PEKANBAU - Sitorus, Debora Sari; Gimin, Gimin; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This Research event will be based on the spirit of nationality that has begun to wear off over time especially among students in SMA Negeri 12 pekanbaru. Formulation of the problem in this research is: